Kontroversi Pemikiran Hadits Mahmud Abu Rayyah: Sebuah Kajian Kritis-Komparatif - Nurkholis Sofwan (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
This paper aims to analyze of Mahmoud Abu Rayyah’s thinking about hadith considered controversial. Although he is an East, but thought much in tune with the group the West. In between the opinions controversial is about standing of hadith that is different from the Sunnah, especially in the writing of hadith, dismantle of establishment equity theory of companions, and doubted the credibility of the companions of Abu Hurayrah. The whole of his opinion is eventually denied by some contemporary Muslim scholars. This paper concludes that the thought of Mahmud Abu Rayyah against hadith has many drawbacks, especially about the history of the writing of hadith and doubts against Abu Hurairah, which contradicts with his own opinion.